The Reliability of Computed Tomography-Derived SYNTAX Score Measurement - (:unkn) unknown (SAGE PUBLICATIONS INC, 2015)
The Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) score (SS) was developed for evaluation of coronary artery disease complexity. We aimed to compare the SS calculated by conventional coronary angiography (CAG) and computed tomography angiography (CTA). Retrospectively, 107 patients were recruited (mean age 55.9 +/- 12.4 years). The SS measured by conventional CAG was divided into 3 groups (group 1 SS 22, group 2 SS > 22 to <32, and group 3 SS 32). The SS calculated by both methods has a high correlation (r = .972 and P < .001). The analysis showed a substantial agreement between both imaging modalities. Computed tomography angiography highly predicted conventional CAG lesions (area under curve 0.96, 95% confidence interval 0.92-0.99, and P < .001). The SS measured by CTA is highly correlated with conventional CAG. Therefore, we propose that prior to coronary revascularization, CTA-derived SS could be used for risk stratification.
Keywords: SYNTAX score; coronary angiography; computed tomography angiography; PERCUTANEOUS CORONARY INTERVENTION; ACUTE CATHETERIZATION; ANGIOGRAPHY; REVASCULARIZATION; STRATEGY; SYNERGY; TAXUS; REPRODUCIBILITY; ASSOCIATION; VALIDATION